Legal pluralism and the place of Syariah courts in the Malaysian legal system - Shuaib, Farid Sufian (2013)
Legal monism namely the idea that there must be one centralised legal system in a state has captivated the legal discourse in the West. The followers of this legal thinking in this part of the world have rehashed the same world view which believes that parallel legal orders would produce uncertainty, inequality and injustice. We could relate such a view with globalisation where sometime "the claimed superiority of Western models of law" could lead to some group in the West becoming what H. Patrick Glenn term as fundamentalists, namely groups that "elevate one truth, or one tradition, to exclusive status, and seek to impose it"